1986
DOI: 10.1021/jf00070a043
|View full text |Cite
|
Sign up to set email alerts
|

Aging of hops and their contribution to beer flavor

Abstract: Two American hop varieties, Washington-grown Cascade and Idaho-grown Hallertauer mittelfriih, were chosen for this aging study and its effect on beer flavor quality. Prior to brewing, hops were refrigerated at 27 °F (fresh), while one portion of the hops from the same bale was aged at 90 °F for 2 weeks (aged I) and another portion for 9 weeks (aged II). Samples at each brewing stage were taken for chemical profile analysis. The finished beers were also submitted for flavor profile evaluations. Geraniol, linalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 7 publications
6
38
0
2
Order By: Relevance
“…Humulene epoxides and humulenols, found in all seven Z. zerumbet accessions, contribute to their herbal, aromatic note as humulene derivatives in hops (Humulus lupulus) contribute to the spicy note in beer and other beverages. [40] Yu et al [41] reported the isolation of a cDNA clone (ZSS1) from Z. zerumbet encoding a-humulene synthase, a key enzyme in zerumbone biosynthesis. This recombinant enzyme on expression in Escherichia coli catalysed the formation the caryophyllenes a-humulene (95%) and b-caryophyllene (5%).…”
Section: Continuedmentioning
confidence: 99%
“…Humulene epoxides and humulenols, found in all seven Z. zerumbet accessions, contribute to their herbal, aromatic note as humulene derivatives in hops (Humulus lupulus) contribute to the spicy note in beer and other beverages. [40] Yu et al [41] reported the isolation of a cDNA clone (ZSS1) from Z. zerumbet encoding a-humulene synthase, a key enzyme in zerumbone biosynthesis. This recombinant enzyme on expression in Escherichia coli catalysed the formation the caryophyllenes a-humulene (95%) and b-caryophyllene (5%).…”
Section: Continuedmentioning
confidence: 99%
“…Identification of marker components, i.e. myrcene, linalool, β-caryophyllene, α-humulene, caryophyllene epoxide, humulene epoxide I, humulene epoxide II, and humulenol II, is based on comparison with published data 4,10,18,29 . Clearly, the combined SFE/ SPE methodology furnishes a sharply defined hop oil fraction only consisting of sesquiterpenoids.…”
Section: )79087 %2( (-7'977-32mentioning
confidence: 99%
“…While there is general agreement on the nature of particular compounds associated with floral and citrus scents, the spicy or herbal aspects of hop character are ill defined. Mainly monoterpene alcohols including linalool, geraniol, and citronellol are key elements of the floral and citrus bouquet of hop aroma 6,[8][9][10]14,[17][18][19] . In addition, several esters of linalool and geraniol, and some uncommon cyclic ethers, such as karahana ether, are often mentioned as contributors to a floral hop aroma in beer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of beer flavour chemistry, several researchers have proposed that geraniol is biotransformed to β-citronellol during fermentation 13,20 . Recently, King and Dickinson 8,9 reported the biotransformation of monoterpene alcohols by yeast metabolism.…”
Section: Introductionmentioning
confidence: 99%